THE NEED ASSESSMENT FOR DIGITAL LITERACY OF TEACHERS UNDER THE OFFICE OF BASIC EDUCATION COMMISSION - Lakthorng, Sonthaya; Kidrakran, Pachoen (Journal of Buddhist Anthropology, 2020)
The purposes of this research were to 1) study current conditions and demands for digital literacy of teachers 2) to assess the needs of digital literacy for teachers. The multistage random sampling technique was used to collect data from 408 teachers under the Office of the Basic Education Commission. This research was divided into 2 steps: 1) inquiring about the current conditions and the demand for digital literacy of teachers. Data were collected by survey. Quantitative data were analyzed using frequency, percentage, mean and standard deviation. Needs assessment in digital literacy for teachers by the priority need index (PNI modified) method. The research found that 1) The current conditions of the teachers under the office of Basic Education Commission overall digital literacy were at the medium level ( = 2.71, S.D. = 1.13). When considering each aspect, it was found that assess aspect had the highest score ( = 3.14, S.D. = 0.95), while create aspect had the lowest score ( = 2.05, S.D. = 1.12). The demand for digital literacy of the teachers as a whole was at the highest level ( = 4.51, S.D. = 0.79). When considering each aspect, it was found that create aspect had the highest score ( = 4.65, S.D. = 0.69), while assess aspect had the lowest score ( = 4.34, S.D. = 0.72). 2) The results of the assessment of the needs for digital literacy of teachers under the office of Basic Education Commission as a whole scores of PNI modified was 0.66. When considering each aspect, it was found that create aspect had the highest scores (PNI modified = 1.27), followed by safe aspect (PNI modified = 0.82) , understand aspect (PNI modified = 0.74), share aspect (PNI modified = 0.68), use aspect (PNI modified = 0.47), and assess aspect (PNI modified = 0.38)